Observations on the Process Control Factors in the Seafood Plants in Kerala - A., Ramachandran; N., Ranganathan; C.T., Samuel (Fishery Technology, 2025)
Process control factors like freezing time, freezer and cold storage tempera tures, drained weight, packing count and bacterial counts were studied. The products were kept in the plate freezer for significantly varying times. The plate freezer temperature did not show much variation in different factories. Fluctuations in storage temperature were noticed in some factories. Fluctuations in the count were found to be more pronounced in small size grades. Total bacterial counts of frozen shrimps were within specified standards. Vibrio cholerae and Salmonella were absent in the samples.